Effects of organophosphate insecticide, sumithion on histopathology of common carp (Cyprinus carpio) in the natural pond condition - Shira, M; Chowdhury, P; Rahman, MS; Haque, SM; Shahjahan, M (International Journal of Agricultural Research, Innovation and Technology, 2021)
Sumithion is an organophosphorus insecticide, which is widely used in aquaculture ponds for eradication of aquatic insect (mainly tiger bug) prior to release of larvae. This study was conducted to evaluate the effects of an organophosphorus pesticide, sumithion on histoarchitecture of liver and kidney in common carp (Cyprinus carpio) during the period from July to December 2016. It was carried out with four treatments, each with two replications. i.e., ponds with no sumithion (T0), with 0.025ppm sumithion (T1), 0.050 ppm sumithion (T2) and 0.100 ppm sumithion (T3). The water quality parameters, such as pH, dissolved oxygen, total alkalinity, free CO2, nitrate-nitrogen (NO3-N), phosphate-phosphorus (PO4-P) were not affected by sub lethal doses of sumithion but the values were fluctuated significantly in most of the cases between the ponds throughout the study period. In case of histoarchitecture of liver and kidney, normal structure of liver and kidney cells were observed in the controlled and treated fish. Through the histological analysis of liver, small vacuole, enlarge lumen space of hepatopancreas and disrupted hepatopancreas were found in T1. Disrupted hepatopancreas, increasement intracellular space, regeneration of hepatic cell and hemorrhage were observed in T2. Moreover, enlarge lumen space of hepatopancreas, degenerated hepatic cell, disrupted hepatopancreas were observed in T3. After the histological analysis of kidney, degenerated renal corpuscle, enlargement of blood vessel, disrupted hematopoetic cell were observed in T1. Ruptured collecting duct, large vacuole, enlarge intracellular space were observed in T2. Furthermore, enlarge bowman’s space, degenerated hematopoetic cell hemorrhage and ruptured distal tubule disrupted, enlarge intracellular space and necrosis were observed in T3. The present investigation sufficiently emphasizes that sumithion has adverse effects on the major organs like liver and kidney. Int. J. Agril. Res. Innov. Tech. 10(2): 66-75, December 2020